1H and 13C-NMR Spectroscopic Study of Some 1H-4,5-Dihydroimidazolium Salts - Alejandra Salerno; Isabel A. Perillo (Molecules, 2000)
The 1H y 13C-NMR spectra of some 1,3 and 1,2,3-trisubstituted 1H-4,5-dihydroimidazolium salts are analyzed.